Music Teachers's Perceptions of the Effectiveness of the Music Studies of the Malaysian Diploma in Teaching - Mah, Kok Heng (2002)
This study sought to examine the perceptions of music teachers towards the effectiveness of the Music Studies of the Malaysian Diploma in Teaching or better known as the Kursus Diploma Perguruan Malaysia [KDPM] with reference to its teaching-learning strategies, acquisition of classroom-based skills, and music teaching skills. The study was prompted by the growing concern about the performance of college-trained music teachers in general, indicating that the KDPM Music Studies may not have adequately equipped graduating teachers with sufficient teaching skills. Questionnaires and interviews were administered to generate the data required for this study. The interviews were carried out to confirm results gathered through questionnaires and to pursue interesting lines of inquiry as they develop. The study utilised a variety of statistical analysis techniques on the quantifiable data obtained, ranging from descriptive statistics to I-tests and F tests for group differences.The research findings indicate that generally, most of the KDPM music teachers who participated in this study perceived the teaching-learning strategies to be effective and agreed in varying degrees that the KDPM Music Studies had been effective in helping them acquire classroom-based skills and music teaching skills. Though positively perceived, the findings also revealed inadequacies in specific teaching-learning strategies and acquisition of teaching skills such as incorporating the use of technology in music education; catering for integration and variety in classroom teaching; teaching music and movement activities associated with western art music; teaching fingering of notes for the alto recorder; and helping student teachers acquire and form musical concepts through the playing of musical instruments. Statistical tests indicate that there are significant differences of perceptions between groups of respondents in the research sample towards the acquisition of classroom-based skills and music teaching skills. Respondents with the STPM entry qualification perceived the acquisition of classroom-based skills more positively than respondents with the SPM/SPMV entry qualifications. Respondents with prior music qualifications perceived the acquisition of music teaching skills more positively than respondents without prior music qualifications. It is hoped that the findings of the study will contribute towards improving the effectiveness of the KDPM Music Studies and the selection of future candidates attending the programme.